Per una scuola «storico-culturale» (progetto programmatico) - Vitaly V. Rubzov; Arkady A. Margolis; Viktor A. Guružapov (LED Edizioni Universitarie, 2014)
Projecting an Historical Cultural School The Authors (namely the Rector, the Vice-Rector and the Coordinator of the programme in Pedagogy and Educational Sciences of the Moscow State University for Psychology and Education), describe a possible institution of a primary School, following «the historicalcultural conception in psychology» (L.S. Vygotskij). The text is a research report, supported by a grant of the Ministry of Education of the Russian Federation, about the different types of school-institutions, existing in the country, subsequently compared with a programme for the possible new historical cultural school. Due to the intensive process of the formation of new social communities, and therefore of activities, sometimes contrasting, characterizing today's society, has every person, today, to become able of coping with different operating social communities, instead that with a unique type, and of making up different forms and means for transforming society, preserving, at the same time, his personal identity. So has a new school to predispose the conceptualization of these new social cultural forms, in the analogies they present with their historical antecedents. Accordingly, has the process of development of new ethnical historical communities, characterizing society today, to be thought of, as generating a new joint intellectual dimension, intercultural, which becomes the unavoidable condition for performing activities. A school pretending to be defined «historical cultural» has to provide the comprehension and analysis of the sense of processes and events of such historical cultural context.